Blackboard jungle [videorecording (DVD)] - Brooks, Richard, 1912-1992; Ford, Glenn, 1916-2006; Francis, Anne, 1930-2011; Calhern, Louis, 1895-1956; Poitier, Sidney; Morrow, Vic, 1931-1982; Farr, Jamie, 1934-; Farr, Jamie, 1934-; Hunter, Evan, 1926-2005 (Controversial classics., 2005)
Urban drama about an idealistic teacher in a slum area who fights doggedly to connect with his unruly students.